STATE BUDGET OF THE REPUBLIC OF KAZAKHSTAN - Dyussegaliyev M.Zн; Sabirovа R.K; Zinullina A.I; Kenzheshov A.A (Academic Journal of Physical and Chemical Sciences, 2019)
According to the authors, the budget classification of the Republic of Kazakhstan is used to compile and execute budgets and ensure the comparability of budget indicators at all levels of the budget system of the Republic of Kazakhstan. Budget classification is a grouping of revenues and expenditures of budgets of all levels of the budget system and sources of financing deficits of these budgets with assignment of classification codes to objects of classification. To implement the reorientation of the economy, large financial investments are necessary; therefore, important problems are finding sources of structural transformations, determining the correlation between state funds in the form of budget allocations and own funds of enterprises. The state budget as an instrument of economic management has an integrated impact on social production as a financial instrument, as an economic lever and as an incentive. Despite the annual growth of state budget expenditures, their effectiveness decreases.